Lima, uma cidade entre a aristocracia e a plebe (1950-1980) - Pinheiro, Marcos Sorrilha [UNESP] (Universidade do Estado de Santa Catarina, 2011)
The city of Lima has undergone serious changes over the past sixty years. Until the middle of the last century, Lima retained an urban structure similar to that built in the 18th century, during the final decades of its colonial period. This reality began to change with the abrupt onset of migration from the mountain ranges to the coast in 1946. However, rather than changes in its urban plan, Lima underwent a ethnic and social reconfiguration that would bring new color and new cultural and behavioral norms to the Peruvian capital. The arrival of migrants to the city caused a conservative reaction in the local elites, but it also sparked a need for the intelligentsia to develop new ways of thinking about the place of migrants in the space of the city, and on the other hand, to create new representations of the city itself. From being a city isolated from the rest of the country, Lima came to live with a range of cultural and ethnic references. It did so, however, without creating greater opportunities for the integration of the masses within the urban and social logic of the city, thus making clear the separation between the aristocracy and the general populace.
Lima, a City between the aristocracy and the commoners (1950-1980)
Keywords: Lima; Migrations; Social science